“LIVING OFF THE GRID”: THE INFLUENCE OF COMPANION CANINES ON ONE’S QUALITY OF LIFE - Seibel, Emily C (East Carolina University, 2019)
Estimates of individuals experiencing homelessness in the United States range between 549,928-643,067 on any given day (National Coalition for the Homeless, 2018; Green Doors, n.d.). Among those individuals experiencing homelessness, approximately 25% have a companion animal (Petsofthehomeless.org, n.d.). There is not a uniform definition of homelessness and the researcher was intentional to acknowledge that the individual is a person and not their circumstances. Participants in this study were two individuals who identified as "living off the grid" in Durham, North Carolina rather than identifying as homeless. The purpose of the study was to evaluate the influence of companion canines on the quality of life of these two individuals. Data were collected through interviews that were audio recorded. Narrative analysis guided the coding of interviews for qualitative data analysis. Using Maslow's Hierarchy of Needs as a framework to investigate how individuals experiencing homelessness may have a different hierarchy of needs than the original framework suggests. The results revealed for the two individuals, who identify as living off the grid, their hierarchy of needs is more fluid than the original hierarchy framework suggests. Their hierarchy has safety, love and belongingness, and physiological needs intricately interwoven. Findings suggest that these two individuals, who identify as living off the grid, have a stronger desire and need for unconditional love than the rest of the general population and find that love with a companion canine.
Keywords: companion animals; homelessness; living off the grid; quality of life; unconditional love; hierarchy of needs; narrative analysis; case study; Human-animal relationships--North Carolina--Durham; Self-reliant living--North Carolina--Durham; Pet owners--North Carolina--Durham--Attitudes; Homeless persons--North Carolina--Durham